2011
DOI: 10.1021/cg200510y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Defects and Growth Directions in the Formation of Periodically Twinned and Kinked Unseeded Germanium Nanowires

Abstract: Here we show the impact of preferred growth directions and defects in the formation of complex Ge nanowire (NW) structures grown by a simple organic medium based synthesis. Various types of NWs are examined including: straight defect free NWs; periodically bent NWs with precise angles between the NW segments; NWs with mutually exclusive lateral or longitudinal faults; and more complex "wormlike" structures. We show that choice of solvent and reaction temperature can be used to tune the morphology of the NWs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 42 publications
3
46
0
Order By: Relevance
“…no lateral (111) stacking faults are formed. 58 However, for the <112> grown NW containing intrinsic (1 ത 11) longitudinal defects, extrinsic (1 ത 11) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 In summary, crystal recovery of grown and top-down fabricated Ge NWs studied using in-situ TEM has been presented. Using in-situ TEM data supported by MD calculations, we demonstrate that the recrystallization of the Ge NWs is complex and may result in structures having polycrystalline regions, large number of extended crystal defects such as stacking faults, and in some cases full crystal recovery.…”
Section: Resultsmentioning
confidence: 99%
“…no lateral (111) stacking faults are formed. 58 However, for the <112> grown NW containing intrinsic (1 ത 11) longitudinal defects, extrinsic (1 ത 11) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 In summary, crystal recovery of grown and top-down fabricated Ge NWs studied using in-situ TEM has been presented. Using in-situ TEM data supported by MD calculations, we demonstrate that the recrystallization of the Ge NWs is complex and may result in structures having polycrystalline regions, large number of extended crystal defects such as stacking faults, and in some cases full crystal recovery.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the NWs were viewed from near the edge of the copper, Interestingly, outliers with diameters > 25 nm were found to exhibit tortuosity (Supporting Information Figure S2) due to a diameter dependent increase in NW kinking caused by defect driven growth direction changes. 27 The XRD diffractogram shown in Figure 2, taken from a typical Ge NW covered Cu substrate, is indexed with the expected peaks of Cu, Ge. Interestingly, additional peaks were also observed consistent with Cu 3 Ge.…”
Section: Resultsmentioning
confidence: 99%
“…These faults result in a streaking in the inset FFT. 27 Figure 3f is a defect free NW with a <112> growth direction. Due to the scarcity of <112> NWs, we were unable to obtain a high resolution image of the NW seed, however, it is likely that the seed orientation is [200] seed / [112] NW due to the similarity in the d spacings of (400) and (224) Figure S5) showed that the formation of catalytic Cu 3 Ge leads to substantial roughening of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The transfer of crystallographic information from a seed particle to a nanowire opens up the possibility of engineering the structure of Ge nanowires and enabling the tuning of band structure via strain modulation. Kinking and defects in Ge nanowires were also investigated by Geaney et al who used a high boiling point (HBS) method to vary the synthesis temperature to produce straight nanowires consisting of stacking faults (longitudinal and transverse), kinked nanowires and tortuous nanowires 191 . While kinked nanowires may have limited applications outside of three-dimensional electronics 192 , the study of such architectures provides an understanding of how kinks are formed, thus enabling future generations of researchers to more accurately synthesise straight wires of uniform structural integrity.…”
Section: Morphology Control In Ge Nanowiresmentioning
confidence: 99%